THE CONTRIBUTION OF BENDORO PANGERAN HANGEBEHI (BPH) SANDIYO PUTERA AMANGKURAT IV TO THE DEVELOPMENT OF ISLAMIC CIVILIZATION IN THE SULTANATE OF YOGYAKARTA-INDONESIA IN THE 18-19TH CENTURY - Imawan, Dzulkifli Hadi; Usman Jaja, Bashiru Usman Jaja (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2024)
This study discusses the major contribution of Bendoro Pangeran Hangebehi (BPH) Sandiyo to the development of Islamic civilization in Indonesia in the 18-19th century. In 1755, when Mataram Kingdom as one of the major kingdoms in the archipelago split into two by the Giyanti Agreement, BPH Sandiyo and his brother, Sultan Hamengkubuwana I, in the Yogyakarta Sultanate, struggled to restore the kingdom into Mataram Sultanate. This study aims to analyze historical accounts of the contribution of BPH Sandiyo to the development of Islamic civilization in the Yogyakarta Sultanate in the 18th-19th century. The research was conducted using literature review, particularly through a qualitative descriptive study with a historical-analysis to explore data related to the contribution of BPH Sandiyo in Yogyakarta Sultanate. The study revealed that BPH Sandiyo had a considerable contribution to the development of the Islamic Civilization of the Archipelago (Islam Nusantara) of the Sultanate of Yogyakarta in the 18-19 Century through his efforts in establishing an Islamic education center, regenerating ulama and fighters, and generating Islamic literacy.